ANALISIS PENINGKATAN TINGKAT PENGUJIAN ULANG DALAM PROSES UJI LABORATORIUM PRODUK TEKSTIL MENGGUNAKAN METODE FMEA - Afifulloh Afifulloh; Hasbullah Hasbullah (Fakultas Teknik Universitas Tulang Bawang Lampung, 2020)
Third-party laboratories are laboratories that provide analytical services as quality control of an item to be marketed. In its activities, sometimes the results of the analysis produced by the laboratory are not all acceptable because there are analysis results that do not meet the test quality specifications. The purpose of this study is to improve the defect rate on the test results using QC tools and FMEA methods. The findings in this study identify the main root causes are the errors of analysts when doing testing, there are no standard procedures for instrument maintenance, and lack of supervision. The proposed improvements given are personnel training, working instruction for instrument maintenance, logbook for record the activity and tighter supervision. After repairs, the defect rate in the test results can be reduced from 5.72% to 1.02%. Keyword: FMEA, Laboratory, Re-testing, Textiles.